Pengembangan Pangan Lokal Melalui Modifikasi Tepung - Budiarti, Gita Indah; Mardhia, Murein Miksa; Azhari, Ahmad (Universitas Muhammadiyah Yogyakarta, 2019)
People with diabetes mellitus in Gunungkidul are increasing in number. This is caused by excessive consumption of flour-based foods. Communities need to be introduced to alternative food substitutes for flour such as cassava. Besides being able to reduce flour consumption in the community, training and education about non-flour snacks can also increase the income of less productive housewives. The purpose of this activity is to provide education about the dangers of consuming foods containing excessive flour and to train in making flour and food from non-wheat alternative ingredients to ladies of Aisyiyah members in ladies Gunungkidul area. The series of service activities was carry out in the form of counseling on food security and healthy food. The second activity was in the form of training in making flour substitute flour and non-flour processed foods. The evaluation phase was in the form of filling out questionnaires by participants. The results of this activisay are processed foods made from non-modified flour and improved knowledge and skills of the participants